2012
DOI: 10.3390/molecules17044373
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Characteristics and Antioxidant Properties of Crude Water Soluble Polysaccharides from Four Common Edible Mushrooms

Abstract: Four crude water soluble polysaccharides, CABP, CAAP, CFVP and CLDP, were isolated from common edible mushrooms, including Agaricus bisporus, Auricularia auricula, Flammulina velutipes and Lentinus edodes, and their chemical characteristics and antioxidant properties were determined. Fourier Transform-infrared analysis showed that the four crude polysaccharides were all composed of β-glycoside linkages. The major monosaccharide compositions were D-galactose, D-glucose and D-mannose for CABP, CAAP and CLDP, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
30
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(34 citation statements)
references
References 25 publications
2
30
0
2
Order By: Relevance
“…At 0.1 to 1 mg/ml concentration HWP, CAP and HAP scavenged hydroxyl radical in the range of 18.72 to 75.59 %, 14.14 to 54.13 % and 20.4 to 55.2 % respectively. The EC 50 value of these polysaccharides are presented in Table 2 which demonstrated their higher activity than that of crude polysaccharide from Flammulina velutipes (Curtis) Singer (He et al 2012).…”
Section: Evaluation Of Antioxidant Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…At 0.1 to 1 mg/ml concentration HWP, CAP and HAP scavenged hydroxyl radical in the range of 18.72 to 75.59 %, 14.14 to 54.13 % and 20.4 to 55.2 % respectively. The EC 50 value of these polysaccharides are presented in Table 2 which demonstrated their higher activity than that of crude polysaccharide from Flammulina velutipes (Curtis) Singer (He et al 2012).…”
Section: Evaluation Of Antioxidant Activitymentioning
confidence: 99%
“…All three polysaccharides exhibited better superoxide radical scavenging activity than that of crude polysaccharidic fraction from Auricularia auricula (L.) Underw. as evident by its high EC 50 value (>2 mg/ml) (He et al 2012). Hydroxyl radical (OH ), the most toxic among all reactive oxygen species, are mainly responsible for the oxidative injury of biomolecules.…”
Section: Evaluation Of Antioxidant Activitymentioning
confidence: 99%
“…Scavenging abilities of the four polysaccharides isolated from four species of edible mushrooms on hydroxyl radicals were depicted in Figure.5. [28] reported the scavenging abilities on hydroxyl radicals of CFVP and CLDP were not very concentration dependent, at the tested concentration range of 0.125-2.0 mg/mL. At 1.0 mg/mL, the scavenging abilities of CABP, CAAP, CFVP and CLDP on hydroxyl radicals were 37.63%, 16.68%, 16.74% and 30.89%, respectively.…”
Section: Discussionmentioning
confidence: 80%
“…Another study of [28] showed the DPPH radical scavenging assay of IPS extracts of edible mushrooms for CFVP were found to be 71.16% respectively.The reducing capacity of a compound may serve as a significant indicator of its potential antioxidant activity [27]. In this assay, the concentration-dependent profile of reducing power was obvious for all the tested polysaccharides.…”
Section: Discussionmentioning
confidence: 99%
“…In another study, crude polysaccharides isolated from four common edible mushrooms including Agaricus bisporus, Auricularia auricula, Flammulina velutipes and Lentinus edodes were studied. The crude polysaccharides of Agaricus bisporus were the best natural antioxidant [13]. Water extracts from five mushrooms were also analyzed.…”
Section: Antioxidant Activitymentioning
confidence: 99%